THROUGH THE WINDOW: CULTURE, COMMERCE, AND VISUAL ART IN UBUD’S DISPLAY SPACE - Subrata, Ni Putu Eka Trisnasari; Hendrawan, Freddy; Dinata, Ramanda Dimas Surya; Kumala, Ni Putu Riska Putri (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
The commercialization of Ubud has a significant impact on the development of the local economy. However, it has also posed challenges in maintaining a balance between growth and preserving culture and the environment. The influence of increasingly developed modernization has driven Ubud’s economy to create innovations in line with current trends. One indication of this is the emergence of various types of businesses with window display designs to attract potential consumers. This descriptive qualitative research collected data by observing stores in Monkey Forest Road and Goutama Street and used a thematic analysis approach to explore the design elements of window displays and identify their classifications, as well as their implications on Ubud’s cultural identity. Ultimately, there are two categories of window displays that show different approaches and objectives: the environmentally adaptive reuse and the brand identity. The emergence of Ubud's window display designs reflects the implementation of modernization and tradition to meet the demands of the global market. In this point, despite Ubud continues maintaining its rich cultural identity, the presence of window displays creates challenges in terms of preserving cultural values that must be faced wisely.